2013
DOI: 10.1115/1.4025165
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Simulation and Conjugate Heat Transfer Around a Low-Mach Turbine Blade

Abstract: International audienceDetermination of heat loads is a key issue in the design of gas turbines. In order to optimize the cooling, an exact knowledge of the heat flux and temperature distributions on the airfoils surface is necessary. Heat transfer is influenced by various factors, like pressure distribution, wakes, surface curvature, secondary flow effects, surface roughness, free stream turbulence, and separation. Each of these phenomenons is a challenge for numerical simulations. Among numerical methods, lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…It can be concluded that the prediction of the amplitude of pressure oscillations is highly dependent on the grid size, and can be over predicted by a factor of 2 or even 3 ( in the case that the first layer of grid in the solid is as far as 1 mm away from the fluid-solid interface). 13 Considering that the spatial scales of the solid temperature profiles are different in case of steady state or transient oscillatory heat transfer, care has to be taken into account the different requirements for the meshing in these two situations. Here, the knowledge of analytical solutions for transient solid thermal behavior can be used for interpretation, as available from the semi-infinite solid approach.…”
Section: Grid Effect In the Solid Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that the prediction of the amplitude of pressure oscillations is highly dependent on the grid size, and can be over predicted by a factor of 2 or even 3 ( in the case that the first layer of grid in the solid is as far as 1 mm away from the fluid-solid interface). 13 Considering that the spatial scales of the solid temperature profiles are different in case of steady state or transient oscillatory heat transfer, care has to be taken into account the different requirements for the meshing in these two situations. Here, the knowledge of analytical solutions for transient solid thermal behavior can be used for interpretation, as available from the semi-infinite solid approach.…”
Section: Grid Effect In the Solid Regionmentioning
confidence: 99%
“…Unfortunately but no attempt has been made to evaluate the influence of transient heat transfer on characterization of Limit Cycle Oscillations (LCO) and creep life of the combustion system. Duchaine et al [11][12][13] used separate solvers and codes to solve the transport equations in the fluid and solid domains, developing a strategy to couple the solvers in an accurate and stable fashion. In this method, the accuracy of results relies heavily on the coupling and interface data exchange between the flow solver and the solid heat conduction code.…”
Section: Introductionmentioning
confidence: 99%
“…Wall temperatures are unknowns of the problem that are resolved by the coupled simulations. This implies coupling a flow solver with a conduction solver [86] as well as the radiative transfer equation when compression is important, leading to high static temperatures (according to the Stefan-Boltzmann law, radiative heat transfer scales as T 4 ). …”
mentioning
confidence: 99%
“…The energy equation inside the solid domain is solved by the AVTP solver [41]. Spatial discretization is handled with a second-order Galerkin scheme [42] and temporal integration uses a first-order forward implicit scheme.…”
Section: Numerical Set-upmentioning
confidence: 99%